PSIKOANALISIS TREND HIJAB SYAR’I - MAWI KHUSNI ALBAR (Yinyang: Jurnal Studi Islam Gender dan Anak, 2017)
Jilbab is identical to the symbol of a pious woman eventhough it raises a controversy. The topic about jilbab has never cometo a final and in fact, jilbab in Indonesia has grown evolutionarily. Theact of wearing jilbab is influenced by some factors, such as: culture,interpretation of religious doctrines, society, economy, psychology, andglobalization trend. Hijab generally means kerudung(a simple headscarf),or cloth covering woman’s aurat(i.e. parts of the body that should becovered based on Islamic doctrine). Meanwhile, when talking about theveil, one usually refers to the scarf tied around the head, and usuallysubject to Muslim women. Nowadays, the discourse about jilbab coversnot only syari’a concept, but also fashion trend concept as the influenceof modern era and cultural shift existing in the society. Women who wearjilbab psychologically consider jilbab not as a religious duty but as a cultureand habit causing a feeling of discomfort not wearing it. Many progressivewomen keep wearing jilbab for their psychological comfort.